Addition of spironolactone to angiotensin-converting enzyme inhibition in heart failure improves endothelial vasomotor dysfunction: role of vascular superoxide anion formation and endothelial nitric oxide synthase expression - Bauersachs, Johann; Heck, Marina; Fraccarollo, Daniela; Hildemann, Steven K; Ertl, Georg; Wehling, Martin; Christ, Michael (Journal of the American College of Cardiology, 2002)
Objectives - We sought to investigate the effects of adding spironolactone (SP) to angiotensin-converting enzyme (ACE) inhibition on endothelium-dependent vasodilation in rats with chronic heart failure (CHF). - Background - Adding SP to ACE inhibitors reduces mortality and morbidity in CHF. Endothelial vasomotor dysfunction contributes to increased peripheral vascular resistance and reduced myocardial perfusion in CHF. - Methods - Seven days after extensive myocardial infarction (CHF) or sham operation, Wistar rats were treated with placebo, the ACE inhibitor trandolapril (TR, 0.3 mg/kg body weight per day), SP (10 mg/kg per day) or a combination of both for 11 weeks. - Results - Maximal acetylcholine-induced, nitric oxide (NO)-dependent relaxation was significantly attenuated in aortic rings from rats with CHF as compared with sham-operated animals (Rmax44 ± 3% vs. 63 ± 3%). Spironolactone alone had no influence (46 ± 5%) and TR improved NO-mediated relaxation (55 ± 4%), whereas treatment with both completely restored endothelium-dependent vasorelaxation (64 ± 4%). Aortic superoxide formation was significantly increased in rats with CHF as compared with sham-operated animals, but was normalized by treatment with SP or SP plus TR. In addition, aortic messenger ribonucleic acid expression of the oxidase subunit p22phoxin rats with CHF was significantly reduced by SP or TR plus SP. Endothelial NO synthase expression was increased in TR-treated animals. Incubation of isolated porcine coronary arteries with SP dose-dependently attenuated superoxide formation. - Conclusions - Spironolactone added to an ACE inhibitor normalizes NO-mediated relaxation in experimental CHF by beneficially modulating the balance of NO and superoxide anion formation.